Samoa : 2012 Article IV Consultation-Staff Report, Informational Annex, Debt Sustainability Analysis, Public Information Notice, Statement by the Executive Director for Samoa. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
After a moderate recovery in 2010-11, the Samoan economy has shown signs of slowing down amid rising inflation. After two consecutive years of contraction, real GDP has expanded by 2 percent in 2010-11. The Central Bank of Samoa has maintained an accommodative monetary policy to support economic activity. However, continued structural reforms are required to lift Samoa's economic growth and to ensure financial stability. Considerable progress has been made in tapping customary land for productive use.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet